The Membership pf a Religious Bishop in his Religious Institute Canons 705-707 - Waters, Ian Benjamin 1943- (2015)
A member of a clerical religious institute was recently ordained a bishop. Another bishop told him that he is no longer a member of his religious institute now that he is a bishop. What truth is there to such an assertion?